Lectins and ELLSA as powerful tools for glycoconjugate recognition analyses - Wu, Albert M.; Liu, Jia Hau (Glycoconjugate journal, 2019)
Lectins, in combination with our established enzyme-linked lectin sorbent assay (ELLSA) and inhibition study, have been used as powerful tools in many glycoconjugate recognition studies. In this short review, we highlight the following: (i) The recognition profiles of Gal/GalNAc-specific lectins were updated and upgraded. (ii) Based on the cross-specificities of applied lectins, a new classification system was introduced. (iii) Applications of lectins for the detection and identification of N -glycan and/or Tn glycotope in glycoconjugates were intergraded. (iv) The polyvalency of the glycotopes in glycans was found to play a critical role in glycan–lectin recognition. This is an unexplored area of glycobiology and one of the most promising directions toward the coming glycoscience transformation.